Antiaging Effects of a Poly Herbal Extract in Comparison with Vitamin E on Aging Induced Mice - Zena M Qaragholi, Ahmed Rahmah Abu-Raghif, Enas Jawad Kadhim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Herbal medicine has been used from antient times to defy aging as cleopatra used several herbs as a drink or topically and pomegranate was a main herb used in her system, it was named the fruit of immortality. Combining three herbs into one preparation is recommended to increase medicinal benefits while reducing toxicity and to obtain a synergistic effect. In this study we have found that a polyherbal (Apium graveolens, Carthamus tinctorius, Punica granatum) extract from Iraqi origin have gave a stronger effect than vitamin E. Aim: The aim of this study was to evaluate the effect of the poly herbal extract in vitro as an antiaging and antioxidant agent in comparison with vitamin E, which is considered as one of the most potent anti aging agents. Materials and methods: forty mice were orally treated and divided into 4 groups ( all were induced with D- Galactose for aging accept the positive control): the first group was positive control, the second was negative control while the third group was treated with vitamin E, and the last group with the polyherbal extract. Later a number of biochemical tests were conducted to evaluate its effectiveness including; test of catalase, GSH-PX, GHS and oxidative stress parameters Results: Our research showed that treated groups with the herbal extract showed great results compared the group treated with vitamin E. Lower levels of 8-hydroxy-2'-deoxyguanosine (8-OHdG) were shown to be associated with reduced levels of MMP-1 upregulation, collagen loss, and increased levels of Nrf2 nuclear accumulation. The polyherbal extract we found, upregulated Nrf2 and reduced ROS production and oxidative damage by D- Galactose. Conclusion: According to the results of our research, the polyherbal extract may be a promising candidate for the prevention of aging signs induced by the intake of D- Galactose. The antioxidant action of vitamin E (VE) makes it an essential nutrient and an important antioxidant to defy aging. Deficit (VED) of VE leads to central nervous system, reproductive and immunological disorders leading to aging. However, this study showed that the polyherbal extract we used gave much better results than vitamin E in preventing aging signs.